2006
DOI: 10.1182/blood-2005-12-023044
|View full text |Cite
|
Sign up to set email alerts
|

Active MAC-1 (CD11b/CD18) on DCs inhibits full T-cell activation

Abstract: The ␤ 2 integrins are important for transendothelial migration of leukocytes as well as for T-cell activation during antigen presentation. Despite abundant expression of ␤ 2 integrins on antigen-presenting cells (APCs), their functional relevance for antigen presentation is completely unclear. We show here that dendritic cells (DCs) from CD18-deficient mice, which lack all functional ␤ 2 integrins, have no defect in antigen presentation. Moreover, DCs from normal mice express inactive ␤ 2 integrins that do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
130
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 73 publications
10
130
1
Order By: Relevance
“…Similarly, in a MLR, alloantigen-induced T-cell proliferation could be increased by Mac-1 inhibition. 15 In the present study, the inhibition of cathepsin X by 2F12 mAb also markedly enhanced proliferation of PBMC. The proliferation was increased by CA-074, an inhibitor of cathepsins B and X, showing that the effect is attributable to the inhibition of cathepsin X activity and not to non-specific action of the monoclonal antibody.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Similarly, in a MLR, alloantigen-induced T-cell proliferation could be increased by Mac-1 inhibition. 15 In the present study, the inhibition of cathepsin X by 2F12 mAb also markedly enhanced proliferation of PBMC. The proliferation was increased by CA-074, an inhibitor of cathepsins B and X, showing that the effect is attributable to the inhibition of cathepsin X activity and not to non-specific action of the monoclonal antibody.…”
Section: Discussionmentioning
confidence: 60%
“…15,34,35 As mentioned previously, Mac-1 activity interferes with LFA-1 mediated aggregation 30 and it has been proposed that dysregulated adhesion and formation of immunological synapse caused by Mac-1 activity might explain down-regulated T-cell activation. 15 In this regard, it has been proposed that via constitutively active Mac-1 on macrophages, in contrast to functionally inactive Mac-1 on dendritic cells, antigen presentation in vivo is restricted to dendritic cells. 15 As shown in our previous study, the localization of cathepsin X in macrophages differs from that in dendritic cells, 17 which may have an impact on different regulation of Mac-1 receptors in the two cell types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous reports showed that CD11b is able to maintain immunological tolerance and inhibit inflammatory responses by repressing TLR3 signaling in NK cells and TLR4 signaling in macrophages (15,16). Analogously, CD11b, abundantly expressed in DCs, can inhibit DC-primed CD4 + T cell activation and promote peripheral tolerance by breaking Th17 differentiation (17,18). These reports suggested roles for CD11b in the regulation of T cell adaptive immunity.…”
mentioning
confidence: 99%